Suomen bioteknologia-ala: Tilannekuva, kasvu ja kasvun haasteet - Martti Kulvik; Mika Pajarinen; Christoffer Sarin (The Research Institute of the Finnish Economy (ETLA), 2025)
Over 830 companies operate in Finland's biotechnology industry. Together, they generate a total turnover of 7.1 billion euros and employ approximately 19,400 people. Technology and business opportunities are developing particularly rapidly in the field of modern biotechnolo- gy which is based on molecular biology. Over the past 15 years, numerous modern biotechnology companies have been established in Finland. One of the challeng- es facing the growth of these companies is the regula- tory process. Challenges related to sales, marketing, and the functioning of distribution channels have also often become obstacles to growth. If these issues can be successfully addressed, the modern biotechnology sector in Finland has the potential to grow significantly.
Keywords: J22; J30; J45; 330; Biotechnology; Biotech; Significance; National Economy